Pelayanan Jamu Pada Ny.S dengan Peningkatan Kadar Asam Urat dalam Darah Tinggi di Penyehat Tradisional (HATRA) R. Klaten - Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Uric acid is a problem in the elderly, with symptoms of joint and heel pain every time you wake up in the morning, stiff on the fingers and toes and swelling and redness. The incidence of gout in the elderly accounted for 47 cases in Hatra R. One of the actions that can reduce uric acid levels is herbal medicine. Sidaguri types of herbs, kepel and bay leaves containing flavonoids, ethanol and hexane can inhibit the activity of xanthine oxidase enzymes that have the potential to reduce uric acid levels in the blood. The purpose of this study was to determine the service of herbal medicine in Mrs. S with high blood uric acid levels. Methods: This research is a descriptive type with a case study approach to 1 client with characteristics of pain in the right waist to the knee. Data collection techniques using the assessment of herbal services. Data validity test is done by triangulation technique based on source triangulation, namely getting information from the client, family, supporting examinations brought by the client, then technique trangulation is by interview and observation and time triangulation namely by checking the data carried out in an iterative time to get the results of the decline uric acid levels in the blood. Results: The results showed that the client's condition is the level of uric acid in the blood to be normal and the pain in the right knee to heal and be able to walk normally so the problem is resolved. Interventions conducted on the client are assessment, determining the problem with the client, determining planning, providing herbal medicine and evaluating services. The results of the evaluation of the action showed that the problem was resolved by decreasing the level of uric acid in the blood. Conclusion: The service of herbal medicine in Ny.S with increased levels of uric acid in the blood can reduce uric acid levels in the blood.